Kewirausahaan Politik Kepala Daerah: Studi Kasus Program Unggulan Panca “Pinter Rakyate” di Kabupaten Wonogiri - Tri Fauzia, Ofifah (Journal of Politics and Policy, 2024)
Political entrepreneurship is an effort by political actors in the form of leadership innovation to increase public interests as political entrepreneurs. In this research, the innovation created by the regional head, the Regent of Wonogiri, was in the form of the Panca "Pinter Rakyate" Program. The Panca "Pinter Rakyate" program includes free education programs, free school uniforms, awards in the form of scholarships for outstanding youth, management of school infrastructure and programs for educators and education staff. This research uses a qualitative approach with descriptive explanation using data collection techniques through interviews, observation and documentation studies. The method used is a case study that analyzes the Political Entrepreneurship of Regional Heads (Case Study of the Panca "Pinter Rakyate" Flagship Program in Wonogiri Regency). The theory used to carry out the analysis in this research is Israel Kizner's theory of Political Entrepreneurship: Alertness and Discovery. The findings in this research have shown how the political entrepreneurship practices of the Regent of Wonogiri are carried out through the Panca "Pinter Rakyate" flagship program. Then it can be seen the role of Regional Apparatus Organizations in the realization of the Panca "pinter rakyate" program. The Wonogiri Regent's innovation through superior programs brings benefits to the community which are marked by reducing poverty rates, increasing the Human Development Index, and increasing community welfare.